2011
DOI: 10.3748/wjg.v17.i19.2389
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/SDF-1 axis is involved in lymph node metastasis of gastric carcinoma

Abstract: The CXCR4/SDF-1 axis is involved in the lymph node metastasis of gastric cancer. CXCR4 is considered as a potential therapeutic target in the treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 34 publications
7
51
0
Order By: Relevance
“…Overexpression of CXCR4 in gastric cancer cells was associated with the development of peritoneal carcinomatosis, which is induced by dissemination of cancer cells into the peritoneal cavity (20,24). Numerous studies have demonstrated that strong expression of CXCR4 is correlated with aggressive tumor characteristics such as deep invasion, lymph node, and liver metastasis (4,20,(25)(26)(27)(28). Furthermore, several pre-clinical investigations demonstrated that blocking of CXCR4 signaling reduced the size and number of tumor metastases (20,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CXCR4 in gastric cancer cells was associated with the development of peritoneal carcinomatosis, which is induced by dissemination of cancer cells into the peritoneal cavity (20,24). Numerous studies have demonstrated that strong expression of CXCR4 is correlated with aggressive tumor characteristics such as deep invasion, lymph node, and liver metastasis (4,20,(25)(26)(27)(28). Furthermore, several pre-clinical investigations demonstrated that blocking of CXCR4 signaling reduced the size and number of tumor metastases (20,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation showed that the human gastric cancer cells SGC-7901 expressed CXCR4, while UCBMSCs expressed stromal derived factor-1 (SDF-1). The interaction between these two molecules induced the MSCs to migrate into gastric tumor tissues [32]. Nakamizo et al [7] reported that BM-MSCs have a tropism for brain tumors and thus could be used as delivery vehicles for glioma therapy, and BM-MSCs were seen exclusively within the brain tumors regardless of whether the cells were injected into the ipsilateral or contralateral carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…When they screened 40 gastric cancer patient samples, Zhao et al [124] found that CXCR4 mRNA levels were significantly higher in cases with lymph node metastasis than those without; they also found that the CXCR4 protein level was correlated with poorly differentiated lesions, more advanced tumor stage and lymph node metastasis. Further, they reported higher CXCL12 mRNA in lymph nodes in patients with metastatic gastric cancer.…”
Section: Stomachmentioning
confidence: 99%
“…Positive regulator of HER [116] Stomach CXCL12, CXCR4 Metastasis through activation of AKT-mTOR pathway and MMPs, upregulation in lymph node metastasis, strong correlation with tumor development [117,118,124] …”
Section: Cxcr4mentioning
confidence: 99%